PRINCIPALS AND TEACHERS PERCEPTIONS ABOUT THE IMPACT OF SCHOOL CONDITIONS ON EARLY ADOLESCENTS’ MOTIVATION AND ENGAGEMENT IN LEARNING AND THEIR MOTIVATING PRACTICES (IN LOW SOCIO-ECONOMIC DISTRICTS IN SRI LANKA) - Perera, Ruwandika; Hathaway, Tanya (PEOPLE: International Journal of Social Sciences, 2017)
In Sri Lanka, a significant proportion of junior students fail to complete their education and withdraw early from secondary school. This is particularly true of students in low socioeconomic districts. This inquiry sought to investigate principal and teacher perceptions of the school-related conditions and motivating practices that contribute to early adolescents‟ motivation and engagement in learning. The study used a qualitative research design. Participants were recruited using purposive sampling method, from ten government schools, representing type two schools, (Five from each Sinhala and Tamil medium), and located in Monaragala and Nuwara Eliya districts in Sri Lanka. Ten principals and ten teachers agreed to participate in semi-structured interviews. Thematic analysis was used to analyse the data and the theoretical construct of Self-determination theory (SDT) was applied to interpreting the data. The results inform two main themes in relation to the school conditions that impact students‟ motivation and engagement in learning: (1) impact of human conditions and (2) impact of physical conditions. Regarding the practices taken to increase motivation and engagement in learning, three themes were emergent: (1) parent awareness, (2) individual support and (3) short term initiatives. First, it can be concluded that numerous problems exist in relation to school conditions, and second that the practices of principals and teachers do not successfully addressed these problems, particularly in Tamil medium schools. It is suggested that, evidence-based intervention programmes be implemented in the most seriously affected schools to increase student motivation and engagement in learning, and slow attrition rates. It is imperative that future research extends to examine early adolescents‟ motivation and engagement across different subjects.